Hubungan Motivasi Belajar dengan Prestasi Belajar Matematika Siswa Kelas V SD Negeri Daerah Binaan 1 Sumbang Banyumas - Suharti, Suharti; Muslim, Arifin; Sriyanto, Sriyanto (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This researched is aimed to discover the relationship between learning motivation and learning achievement of mathematics subject for 5 graders in Fostered Public Primary School 1 sub-district Sumbang, Banyumas. The methods used for this research was corelation with quantity approach. The population was 387 students of grade V from 11 public primary schools, while 197 students were used for sampling. The samples were collected using probability sampling. The technique used for data collection were a non-test technique in form of learning motivation Â questionnaire and a test technique in form of essay questions. The result of this research shows that there is a relationship between learning motivation and learning achievement with rhitungrtabel = 0,3490,1398 with significance value 0,0000,05, so it is said as significant and applicable to the population. Regression test result shows that Y` = a + bX with the value of a = 7,861, which means if learning motivation = 0, so learning motivation = 7,861.Â The coeficient of b = 0,611, which means if learning motivation is raised up to 1 denomination, so learning motivation will be raised up to 0,611 denomination as well. These datas show that if the value of X is raised, the value of Y will be raised as well for both of them has positive and same direction of relationship.